ANALISIS KEMAMPUAN PENDAPATAN PETANI KARET DALAM MEMENUHI BIAYA KEBUTUHAN RUMAHTANGGA DI SUMATERA SELATAN - Tirta Jaya Jenahar (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2005)
The objecting of this study is to analysis the ability of income farmer to handle need of household and how to increasing ability of farmer household income. The data are collected multi stage sampling for district, sub district and village randomly for farmer household and the data collection is on October 2004 till August 2005. The instrument is interview for 360 farmers household 210 non-modern farmers and 150 modern framers as sample at 12 villages are representative of Musi Rawas, Muara Enim and Musi Banyuasin District in South Sumatra.The result indicate that the average income of modern and non-modern farmers able to handle ned of household about 95% and 87%. The ability of income will be increasing through increasing income with used leisure time and intercrop.